Study of Correlation the Implementation of Norms Small Happy and Prosperous Family with Difficulty Learning In 8th SMP Nurul Falah Srono Banyuwangi, East Java, Indonesia - Marhain, Sri Sedar; Arifin, Miftahul (International Journal for Educational and Vocational Studies, 2020)
Families have the role and primary responsibility for the care and protection of children from class SRONO culture, education, values and norms of community life begin in the family environment. For the perfect and harmonious development of children's personalities, they must grow in the family environment in a climate of happiness, love and understanding. What is the correlation between the implementation of the norms of happy and prosperous small families with learning difficulties in class VIII semester II SMP Nurul Falah Srono. This study uses a quantitative approach with the method used to analyze data using the tetrachoric correlation statistical method. The results of his research that there is a correlation between the norms of happy and prosperous small families with the learning difficulties of VIII semester II semester students of Nurul Falah Srono Middle School, the level of relationship obtained by 0.542 lies between 0.400 to 0.600 which means the level of correlation is sufficient.